Application of single wireless holter to simultaneous EMG, MMG and EIM measurement of human muscles activity - Vavrinský, Erik; Svobodová, Helena; Donoval, Martin; Daricek, Martin; Kopáni, Martin; Miklovič, Peter; Hořínek, František; Telek, Peter (Lékař a technika, 2018)
This paper describes application and design of wireless holter with innovative functionality, used it in field of human muscle monitoring. In our experiments we monitored EMG (electromyography), MMG (mechanomyography) and EIM (electrical impedance myography) all by single device. It is first time when these all parameters were monitored simultaneously taking advantage of the holter device data output in order to find the signals interconnection. Our data were compared with normally used medical device and signal quality was verified.
Keywords: elektrická stimulace; diferenciální diagnóza; Diagnosis, Differential; Myography; myografie; Muscle, Skeletal; monitorování fyziologických funkcí; Humans; elektromyografie; kosterní svaly; Monitoring, Physiologic; Electric Stimulation; Muscular Diseases; nemoci svalů; Electromyography; lidé